2011
DOI: 10.1007/s11240-011-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cinnamoyl CoA reductase and cinnamyl alcohol dehydrogenase gene promoters from Leucaena leucocephala, a leguminous tree species, and characterization of tissue-specific activity in transgenic tobacco

Abstract: Promoter sequences of a 795 bp cinnamoyl CoA reductase (LlCCR) and 1,882 bp cinnamyl alcohol dehydrogenase (LlCAD) genes were isolated from Leucaena leucocephala, a leguminous tree species by genome walking, and analysed using bioinformatics tools. This revealed presence of cis-elements such as AC-boxes, XYLAT, WRKY, and MYB binding sites in addition to CAAT and TATA boxes. For functional characterization, each of LlCCR and LlCAD promoter sequences were fused to b-glucuronidase (GUS) reporter gene, immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…GSE2 acts as a regulator only in the sheaths and stem tissues and has a weaker effect on gene expression. Thilmony and Cook [61] characterized the promoter OsGEX2, which is expressed in the sperm cells of mature rice pollen • Leucaena (Leucaena leucocephala): Prashant et al [62] isolated 2 specific promoters, LlCCR and LlCAD, that act in the vascular tissues of leaves, roots, and stamens • Soybean (Glycine max): In the literature, several studies have shown specific promoters isolated from soybean; some of them have been used in transgenic research. Freitas [63] isolated the promoter SPB2 (sucrosebinding protein), which guides the expression of reporter genes in the vascular tissue of transgenic tobacco.…”
Section: Tissue-specific Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…GSE2 acts as a regulator only in the sheaths and stem tissues and has a weaker effect on gene expression. Thilmony and Cook [61] characterized the promoter OsGEX2, which is expressed in the sperm cells of mature rice pollen • Leucaena (Leucaena leucocephala): Prashant et al [62] isolated 2 specific promoters, LlCCR and LlCAD, that act in the vascular tissues of leaves, roots, and stamens • Soybean (Glycine max): In the literature, several studies have shown specific promoters isolated from soybean; some of them have been used in transgenic research. Freitas [63] isolated the promoter SPB2 (sucrosebinding protein), which guides the expression of reporter genes in the vascular tissue of transgenic tobacco.…”
Section: Tissue-specific Promotersmentioning
confidence: 99%
“…Promoter sequences can be analyzed using several computational tools currently available, allowing the identification of putative TFs, which are analyzed by alignment using databases available online and further characterization in silico [60,62]. Some database sites are shown in Table 2.…”
Section: Analysis Of Promotersmentioning
confidence: 99%
“…P-box, a motif implicated in gibberellin response was found at +2. Overall, it is noted that similar sets of cis-acting elements were also reported from promoters of other lignin genes such as cinnamoyl-CoA reductase (CCR) and cinnamyl alcohol dehydrogenase (CAD) (Prashant et al 2012;Lacombe et al 2000).…”
Section: Isolation and Analysis Of Promotermentioning
confidence: 64%
“…Nevertheless, the most abundant motifs detected were the cis-elements involved in the response to biotic and abiotic stresses, including TC-rich repeats, LTR, W-BOX, ARE, HSE and MBS ( Jin et al, 2014 ). At the same time, we still found that there were putative cis -acting regulatory elements involved in the MeJA-responsiveness, namely CGTA-motif, TGACG-motif and CCAAT-motif ( Matton et al, 1990 ; Prashant et al, 2012 ; Cheng H. et al, 2013 ). TCA-element clustered in the promoters of CmFDH1, CmADH1, CmADH3, CmADH5, CmADH7-9 and CmADH12 , and S ARE were also present in CmADH3 promoter, both of which were cis -acting regulatory element involved in the SA-responsiveness ( Prashant et al, 2012 ; Cheng H. et al, 2013 ).…”
Section: Resultsmentioning
confidence: 88%
“…At the same time, we still found that there were putative cis -acting regulatory elements involved in the MeJA-responsiveness, namely CGTA-motif, TGACG-motif and CCAAT-motif ( Matton et al, 1990 ; Prashant et al, 2012 ; Cheng H. et al, 2013 ). TCA-element clustered in the promoters of CmFDH1, CmADH1, CmADH3, CmADH5, CmADH7-9 and CmADH12 , and S ARE were also present in CmADH3 promoter, both of which were cis -acting regulatory element involved in the SA-responsiveness ( Prashant et al, 2012 ; Cheng H. et al, 2013 ). ERE, ethylene-responsive element, was found in the promoter of CmFDH1, CmADH1, CmADH2, CmADH3, CmADH5, CmADH6, CmADH8 and CmADH12.…”
Section: Resultsmentioning
confidence: 88%